The Rights to Freedom of Belief Based on Pancasila - Waringga, Kristoforus Farian; Muchtar, Adjuan Sudjana (Unisia, 2021)
Pancasila is the legal basis and ideology of Indonesia, which regulates all existing laws, including the freedom of belief. The Indonesian state was founded by national warriors of ethnic, language, cultural, customary, and religious diversity, thereby necessitating the people to exhibit mutual respect and appreciation. Therefore, this research aims to discover the meanings, values, and appropriate practices of the first Pancasila precepts in order to guarantee the right to freedom of belief, religion, and worship. The legal or normative juridical research method was employed by observing previous events and cases and analyzing them with a statutory approach. Subsequently, the results showed that the right to freedom of religion is regulated in the first precepts of Pancasila, where every citizen has the right to choose, embrace, and practice worship according to their beliefs. Hence, every society should cultivate a sense of unity in diversity by respecting and appreciating other religions, as the existence of all beliefs is guaranteed by law and the state.